The Contribution of Farmer Family Housewives in Increasing Family Income - Kaseng, Ernawati S. (Universitas Negeri Makassar, 2025)
The purpose of the article research is to describe the contribution of housewives of farming families in increasing family income, and the efforts that underlie the dual role of housewife in the public and domestic spheres. The research method used is qualitative descriptive method. Primary data retrieval techniques are through observation, in-depth informant interviews, and secondary data are retrieved through documentation tracking. The non-probality sampling technique was used and then purposive sampling was drawn, based on several criteria to see the contribution of the dual role of farmer wives in increasing income as housewives. The research output of the article shows that the dual role of housewife farming families in the public sphere, such as participating in making a living by working with their husbands in cultivating their farm land to earn income, both money and goods in order to meet family needs. Meanwhile, the dual role of housewife for farming families in the domestic realm, namely in terms of supporting family welfare needs, by managing family needs every day, and doing household chores such as taking care of children and husbands, cooking, washing and so on. Then the obstacles faced by the dual role of housewife farming families to improve their family welfare, including lack of employment, lack of human resources, and minimal level of education and capital, and the development of technology that replaces human labor.